2021
DOI: 10.1101/2021.04.28.441750
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ability of known colorectal cancer susceptibility SNPs to predict colorectal cancer risk: A cohort study within the UK Biobank

Abstract: Colorectal cancer risk stratification is crucial to improve screening and risk-reducing recommendations, and consequently do better than a one-size-fits-all screening regimen. Current screening guidelines in the UK, USA and Australia focus solely on family history and age for risk prediction, even though the vast majority of the population do not have any family history. We investigated adding a polygenic risk score based on 45 single-nucleotide polymorphisms to a family history model (combined model) to quant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…A value of 0.5 suggests that the tool is performing no better than chance, while a value of 1 is obtained when cases and non-cases are perfectly separated. The range of reported AUC associated with published PRS ranged from 0.584 to 0.678 for breast cancer [6][7][8][9][10][11][12], 0.591 to 0.769 for prostate cancer [8,10,13], 0.609 to 0.708 for colorectal cancer [8,10,14,15], and 0.52 to 0.846 for lung cancer [8,10,13,16]. In a study by Jia et al looking at eight common cancers in the UK Biobank population-based cohort study (n=400,812 participants of European descent), the observed AUC ranged from 0.567 to 0.662 [10].…”
Section: Introductionmentioning
confidence: 99%
“…A value of 0.5 suggests that the tool is performing no better than chance, while a value of 1 is obtained when cases and non-cases are perfectly separated. The range of reported AUC associated with published PRS ranged from 0.584 to 0.678 for breast cancer [6][7][8][9][10][11][12], 0.591 to 0.769 for prostate cancer [8,10,13], 0.609 to 0.708 for colorectal cancer [8,10,14,15], and 0.52 to 0.846 for lung cancer [8,10,13,16]. In a study by Jia et al looking at eight common cancers in the UK Biobank population-based cohort study (n=400,812 participants of European descent), the observed AUC ranged from 0.567 to 0.662 [10].…”
Section: Introductionmentioning
confidence: 99%